Chromosome 1q21 gain is an adverse prognostic factor for newly diagnosed multiple myeloma patients treated with bortezomib-based regimens - Liu, Xiao; Jia, Shuangshuang; Chu, Yuping; Tian, Biao; Gao, Yaya; Zhang, Chunyan; Zheng, Yanhua; Jia, Weijing; Liu, Xiangxiang; Yuan, Ruifeng; Zhang, Na; Feng, Juan; et al. (Frontiers in Oncology, 2022)
Chromosome 1q21 aberration is one of the most common cytogenetic abnormalities in multiple myeloma, and is considered an important prognostic factor. The present study analyzed the clinical relevance and prognostic impact of 1q21 gain in 194 patients with newly diagnosed multiple myeloma treated with bortezomib-based regimens. 1q21 gain was detected in 45.9% (89/194) of patients, and those with 1q21 gain had a worse prognosis. Strikingly, our results showed that excluding the effects of other coinciding genetic anomalies, patients carrying at least four copies of 1q21 had worse survival outcome. Moreover, del(13q) strongly correlates with 1q21 gain, and the coexistence of del(13q) and 1q21 gain plays an important role in reducing PFS and OS times. Therefore, 1q21 gain should be considered a high-risk feature in multiple myeloma patients treated with a bortezomib-based regimen.